2006
DOI: 10.1007/s10658-005-5996-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Relationship of Plasmopara halstedii Isolates Differing in Pathogenicity and Geographic Origin Based on ITS Sequence Data

Abstract: Sequence parts of the internal transcribed spacer (ITS) region of nuclear ribosomal DNA were analysed to screen for the intraspecific variability of a non-coding genomic region in 15 Plasmopara halstedii populations of different pathotype and geographic origin. Samples revealed uniformity in a ca. 790 Bp fragment comprising of the ITS-1, 5.8S and front parts of the ITS-2. In contrast, clear differences were found in a ca. 810 Bp fragment of the ITS-2 thus allowing differentiation between populations of pathoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Either the isolates used in our study were different from the ones used by Delmotte et al (2008), or the intrarace variance in the EST-derived marker may explain the different results reported. However, the distinctiveness of the 7xx races compared to those of races 100 or 3xx has recently been shown based on ITS sequence data (Spring et al, 2006). No correlation was detected between aggressiveness traits (Table 2) and EST genotypes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Either the isolates used in our study were different from the ones used by Delmotte et al (2008), or the intrarace variance in the EST-derived marker may explain the different results reported. However, the distinctiveness of the 7xx races compared to those of races 100 or 3xx has recently been shown based on ITS sequence data (Spring et al, 2006). No correlation was detected between aggressiveness traits (Table 2) and EST genotypes.…”
Section: Discussionmentioning
confidence: 93%
“…Today, the total P. halstedii races can overcome the resistance genes in seven of the nine downy mildew differential lines of H. annuus, and the Pl2 and Pl6 genes have each been overcome by eight races . Moreover, Spring et al (2006) differentiated between populations of pathotypes 100, 310 and 330 and a group of populations representing pathotypes 700, 701, 703, 710 and 730. Also, Delmotte et al (2008) identified three genetically differentiated groups of isolates organized around the first three races described in France: 100, 710 and 703.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Table 2 Fatty acid composition (ratio of total peak area) assayed by GC analysis of sporangia and sporangiophores of P. angustiterminalis propagated on sunflower lines and (Thines 2007). The total ITS length (3190 bp) exceeded the known size found so far within the Plasmopara genus by >20% (Spring et al 2006;Voglmayr et al 2006). For the phylogenetic analysis only conserved regions were used in the model to exclude the influences of in/dels (Mitchell and Zuccaro 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas this primer has so far not found use in oomycete community studies, it has been used successfully to amplify the DNA of a wide range of oomycetes in phylogenetic research (Spring et al 2006, Thines 2007.…”
Section: Introductionmentioning
confidence: 99%